Tempo de muito chapéu e pouca cabeça, muito pasto e pouco rastro: ação estatal e suas implicações para comunidades tradicionais no Parque Nacional dos Lençóis Maranhenses. - DIAS, Roseane Gomes (2017)
The present thesis is the result of a set of research investments in three locations at Lençois Maranhenses National Park, in Barreirinhas: Tratada dos Carlos, Tucuns and Ponta do Mangue. It pursued to understand how the territorialisation of those traditional communities has been processed and the changes in those groups social and economic organization, after the action of the State environmental department agents, since the creation of that integral protection conservation unit in 1981. Ethnographic work, consolidated through direct observation and participation in family groups everyday events allowed to identify the territorial conducts which promoted the consolidation of a way of life, from the interaction between humans and the environment. Families practices, before and after the establishment of the National Park, enabled the consolidation of social organizations which are being affected as a result of the introduction of new rules for the use of resources and permanence in the National Park by ICMBio. Inspection activity by the environmental department agents, rigorously based on norms related to integral protection conservation units has generated social and environmental conflicts involving the public agents and family groups. In such a context of prohibitions, restrictions and sanctions imposed to the families, everyday forms of resistance (SCOTT, 2002) have been used by farmers, fishermen, livestock raisers and gatherers as a form of opposing such action, or as strategies to remain developing activities which provide their material, social and symbolic needs. Underlying such form of action by the environmental department agents, characterized by constant constraints to the families‟ social and economic organisation, a disguised gradual disengagement from that conservation unit may be identified, with no reparation, dispossession or Settlement Term having effectively been performed by the State.